Analysis of Inpatients Food Leftover at Sanglah Hospital Bali Province - Ni Luh Partiwi Wirasamadi; Kadek Tresna Adhi; I Wayan Weta (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: Foods leftover is still very common in many hospitals in Indonesia. Minimum standard of hospitals require that foods leftover of patient is not more than 20%. The aim of this study was to determine the number and cost wasted due to the foods leftover of patient. Methods: The study was cross-sectional involving 68 inpatient subjects in the 1st, 2nd and 3rd ward class and hospitalized up to 10 days and had regular food with a 10-day menu cycle. Data of foods leftover were obtained by three methods: observation, medical records and interview. Foods leftover were measured by Visual Comstock method with the scale of 6 points. Age, sex, length of stay, ward classes, and types of patients’ diseases were obtained from medical records. Patient’s perception of food appearance and taste were gained through interviews. Data were analyzed by independent sample t-test and one-way ANOVA. Results: Average number of patients’ food leftover amounted to 14.79%. Patients who left foods were mostly women, aged 50-64 years, hospitalized in the class 2nd and 3rd with a length of stay ≤5 days. Those who had good perception on appearance and taste of the food tended to leave less food leftovers. The average cost of meal wasted a day was Rp 2,939 per patient. There were significant different leftover foods according to gender, age group, length of stay, ward classes, and the patient’s perception (p<0,05), whereas there were no significant different leftover foods according to the type of diseases and the menu cycles (p>0,05). Conclusion: Average number of patients’ food leftover at Sanglah Hospital Denpasar has satisfied hospital minimum standard (less than 20%) with an average daily cost of meal wasted was Rp 2,939 per patient.